Budowa ciała chłopców i dziewcząt województwa lubuskiego w wieku 7-18 lat. Tendencje zmian = Body build trends in boys and girls aged 7-18 in the Lubuskie Voivodeship - Asienkiewicz, Ryszard; Wandycz, Artur (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Objective: This study aimed to analyse the body build of boys and girls in the Lubuskie Voivodeship and to highlight the changing trends from 2002 to 2017. Material and Methods: The research involved 11,760 schoolchildren (5,680 boys and 6,080 girls) aged 7-18 years, observed from 2015 to 2017 in randomly selected primary and secondary schools in the Lubuskie Voivodeship.
Keywords: uczniowie; budowa ciała; tendencje zmian; schoolchildren; body build; trends